Kajian Reaksi Oksidasi Senyawa 2,6,6-Trimetil Bisiklo[3.1.1]Hept-2-Ena Menggunakan Aliran Gas Oksigen Dan Zeolit Nax - Nohong Nohong (Biology Department, Mathematics and natural science, Tadulako University, 2009)
Oxidation reaction has been done oxidation on ά-pinena (2,6,6-trimetil bisiklo[3.1.1]hept-2-ena) utilizing oxygen gas flow and NaX zeolite as catalyst. The aim of the research is to study both the application of oxygen flow as oxidant and zeolite NaX as catalyst to produce the oxidation product that can be controlled by regioselektif. The Reaction product and The progress of oxidation reaction was observed using Chromatography gas (GC), Infra red Spectrofotometry and gas chromatography gas – mass spectrograph (GC-MS). The result showed that the main reaction product was 2,6,6-trimetil bisiklo[3.1.1]hept-1-en-3-on. The temperature Condition and the concentration of Zeolite were 110oC and 4% (m/v) respectively. The reaction mechanism for formation 2,6,6-trimetil bisiklo [3.1.1]hept-1-en-3-was estimated conduct through transition state 2,6,6-trimetil bisiklo[3.1.1]hept-1-en-2-hidroperoksida free one molecule of water to form keton carbonil compound.